Wear behavior of gas tungsten arc deposited FeCr, FeCrC, and WC coatings on AISI 1018 steel - Yimaz, Serdar Osman (Elsevier Science Sa, 2006)
AISI 1018 low-alloy steel was coated by using FcCr, FeCrC and WC-FeCrC alloy powders and the gas tungsten arc processing (GTA) method. The friction and the wear behavior of the coated surfaces were tested under dry sliding conditions against WC-Co slider. The dry sliding wear tests were performed on a pin on disc machine, and the influence of sliding speed on wear rate was determined. The test results indicate that the wear resistance of AISI-1018 steel can be improved by means of GTA surface alloying, and high chromium ferrochromium powders can be used for high speed applications to reinforce the surface of a low carbon steel with a WC particulate mixture. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: GTA; dry sliding wear; surface coating